A Study on Prevalence and Characterization of Bacillus cereus in Ready-to-Eat Foods in China - Yu, Shubo; Yu, Pengfei; Wang, Juan; Li, Chun; Guo, Hui; Liu, Chengcheng; Kong, Li; Yu, Leyi; Wu, Shi; Lei, Tao; Chen, Moutong; Zeng, Haiyan; et al. (Frontiers in Microbiology, 2020)
Bacillus cereus is widely distributed in different food products and can cause a variety of symptoms associated with food poisoning. Since ready-to-eat (RTE) foods are not commonly sterilized by heat treatment before consumption, B. cereus contamination may cause severe food safety problems. In this study, we investigated the prevalence of B. cereus in RTE food samples from different regions of China and evaluated the levels of bacterial contamination, antibiotic resistance, virulence gene distribution, and genetic polymorphisms of these isolates. Of the tested retail RTE foods, 35% were positive for B. cereus, with 39 and 83% of the isolated strains harboring the enterotoxin-encoding hblACD and nheABC gene clusters, respectively. The cytK gene was present in 68% of isolates, but only 7% harbored the emetic toxin-encoding gene cesB. Antimicrobial susceptibility testing revealed that the majority of the isolates were resistant not only to most β-lactam antibiotics, but also to rifamycin. Multilocus sequence typing (MLST) revealed that the 368 isolates belonged to 192 different sequence types (STs) including 93 new STs, the most prevalent of which was ST26. Collectively, our study indicates the prevalence, bacterial contamination levels, and biological characteristics of B. cereus isolated from RTE foods in China and demonstrates the potential hazards of B. cereus in RTE foods.